Operation Control Technology and Application of All-clean Energy Power Supply in Provincial Power Grid - Gang ZHU; Yanhe LI; Zhen ZHANG; Yourui XU (Zhongguo dianli)
Electricity plays an important role in energy transformation. The future energy transformation will show the trend of clean, low carbon and electrification. This paper mainly introduces the operation control technology and application of all-clean energy supply in provincial power grid. Firstly, this paper introduces the technical problems faced by the power grid to achieve all-clean energy supply; secondly, the power and electricity balance equation of the power grid under the condition of all-clean energy supply is analyzed; thirdly, based on the output constraints of the power grid and Hydropower units, dispatching generation scheduling optimization function is analyzed. Finally, taking the clean energy power supply successfully realized in Qinghai Province in recent three years as an example, this paper analyzes the feasibility and main implementation process of the clean energy in the provincial power grid from the perspective of engineering practice, and discusses the innovative connotation of the three clean energy power supply in technology and transaction mode. The practice and exploration of all-clean energy power supply can provide practical experience for improving the multi-energy complementary coordination control and new energy absorption capacity of power grid, promoting the development of clean energy, and providing meaningful reference for the power grid to carry the new energy revolution.